ANALISIS KESETARAAN GENDER DI UNIVERSITAS HALUOLEO - Komang Arwini Puspita Dewi; Abd. Azis Muthalib; Ulfa Matoka (Universitas Halu Oleo, 2022)
One indicator of good government in the success of each institution is the creation of gender equality at every level. This study aims to determine the participation and access of women in haluoleo university institutions. The type of research used is qualitative research. The type of data used in this research is secondary data. Secondary data is gender-disaggregated data which includes the number of male and female participation, namely: 1) students, 2) lecturers, 3) administrative staff, and 4) structural officers in all faculties and programs within the scope of Haluoleo University. Based on the objectives to be achieved in this study, the method that will be used is the Pathway Gender Analysis Method, which is an analytical method that is comparing and not measuring. The gender analysis method is a method used by planners which aims to make improvements from a situation to a better situation. The analysis technique used is called the Gender Analysis Pathway (GAP).